179. Whole brain radiotherapy with hippocampal sparing and Simultaneous Integrated Boost for patients with one to four metastases with Helical Tomotherapy. (December 2018) - Iacco, M.; Zucchetti, C.; Dipilato, A.C.; Lupattelli, M.; Podlesko, A.M.; Fulcheri, C.; Marcantonini, M.; Reggioli, V.; Aristei, C.; Tarducci, R.
Abstract: Purpose: Hippocampal avoidance during irradiation is hypothesized to reduce the risk of memory function decline. This study is designed to evaluate the dosimetric and clinical results of Helical Tomotherapy (HT) whole brain radiotherapy with hippocampal avoidance (WBHA) and Simultaneous Integrated Boost (SIB). Methods: A total of 19 patients with 1 to 4 brain metastases (BM), diameter ⩽3 cm, absent or controlled extracranial disease were planned for WBHA with SIB using HT, from September 2014 to November 2017. The hippocampus was contoured on diagnostic T1-weighted magnetic resonance imaging (MRI) which had been registered with the planning CT image set. The hippocampal Planning Risk Volume was generated using a 5 mm uniform margin around the hippocampi. The BM were contoured on T1-weighted MRI registered with the planning computed tomography (CT), and the BM-PTV was the BM expanded 3 mm in all directions. The whole-brain planning target volume (WB-PTV) was defined as the whole-brain tissue volume, expanded 3 mm in all directions, minus hippocampal PRV and BM-PTVs. HT plans were generated with the following parameters: field width set at 1.05 cm, pitch 0.287, modulation factor (MF) set in the range 2–3 leading to a final value of 2 on average (range 1.3–2.8). Prescription dose was 30 Gy for WB-PTV and 40 Gy for each BM-PTVs in 10 fractions. Results: Dosimetric result were reported in Table 1: all the parameter analysed were very promising and in accord to the RTOG 0933 trial[1] . The mean treatment time was 8.7 min (range 6.5–12.6 min). Conclusions: HT plans achieved three objectives: quite homogeneous whole brain dose distribution; conformal hippocampal avoidance; and high coverage to the BM.